ANALISIS PENDAPATAN USAHATANI PADI SAWAH DESA PEWUNU KECAMATAN DOLO BARAT KABUPATEN SIGI - Siti Mutmainnah; Arifuddin Lamusa; Siti Yuliaty Chansa (Universitas Tadulako, 2022)
The purpose of this study was to determine the income of rice farmers in Pewunu Village, Dolo Barat District, Sigi Regency. carried out in Pewunu Village, Dolo Barat District, Sigi Regency from November 2020 to January 2021. Determination of sample farmer respondents taken as many as 32 people from the total population of lowland rice farmers with the consideration that these 32 respondents can represent the population of lowland rice farmers in the village Pewunu. The data used are primary data and secondary data. The analysis used in this research is income analysis. The results of the income analysis show that the average income received by lowland rice farming in Pewunu Village, Dolo Barat District, Sigi Regency is Rp. 29,223,124 per season with an average income of Rp. 41,861,250 per season minus the total cost of Rp. 12,638,126 per season.